NMR characterization and evaluation of antibacterial and antiobiofilm activity of organic extracts from stationary phase batch cultures of five marine microalgae (Dunaliella sp., D. salina, Chaetoceros calcitrans, C. gracilis and Tisochrysis lutea). (August 2019) - Iglesias, M José; Soengas, Raquel; Probert, Ian; Guilloud, Emilie; Gourvil, Priscillia; Mehiri, Mohamed; López, Yuly; Cepas, Virginio; Gutiérrez-del-Río, Ignacio; Redondo-Blanco, Saúl; Villar, Claudio J.; Lombó, Felipe; et al.
Abstract: The chemical composition of five marine microalgae ( Dunaliella sp., Dunaliella salina, Chaetoceros calcitrans, Chaetoceros gracilis and Tisochrysis lutea ) was investigated through nuclear magnetic resonance (NMR) spectroscopic study of the soluble material obtained by sequential extraction with hexane, ethyl acetate (AcOEt) and methanol of biomass from stationary phase cultures. Hexane extracted the major lipids present in the microalgae during the stationary phase of growth, which correspond to storage lipids. Triacylglycerols (TGs) were the only storage lipids produced by Dunaliella and Chaetoceros . In contrast, T. lutea predominantly stored polyunsaturated long-chain alkenones, with sterols also detected as minor components of the hexane extract. The molecular structure of brassicasterol was determined in T. lutea and the presence of squalene in this sample was also unequivocally detected. Monogalactosyldiacylglycerols (MGDGs) and pigments were concentrated in the AcOEt extracts. C. calcitrans and D. salina constituted an exception due to the high amount of TGs and glycerol produced, respectively, by these two strains. Chlorophylls a and b and β-carotene were the major pigments synthesized by Dunaliella and chlorophyll a and fucoxanthin were the only pigments detected in Chaetoceros and T. lutea . Information concerning the acyl chains present in TGs and MGDGs as well as the positional distribution of acyl chains on the glycerol moiety was obtained by NMR analysis of hexane and AcOEt extracts, with results consistent with those expected for the genera studied. Fatty acid composition of TGs in the two Dunaliella strains was different, with polyunsaturated acyl chains almost absent in the storage lipids produced by D. salina . Except in C. calcitrans, the polar nature of soluble compounds was inferred through the relative extraction yield using methanol as the extraction solvent. Glycerol was the major component of this fraction for the Dunaliella strains. In T. lutea 1, 4/2, 5-cyclohexanetetrol (CHT) and dimethylsulfoniopropionate (DMSP) preponderated. CHT was also the major polyol present in the Chaetoceros strains in which DMSP was not detected, but prominent signals of 2, 3-dihydroxypropane-1-sulfonate (DHSP) were observed in the 1H NMR spectra of methanolic extracts. The presence of DHSP confirms the production of this metabolite by diatoms. In addition, several other minor compounds (digalactosyldiacyglycerols (DGDGs), sulphoquinovosyldiacylglycerols (SQDGs), amino acids, carbohydrates, scyllo -inositol, mannitol, lactic acid and homarine) were also identified in the methanolic extracts. The antibacterial and antibiofilm activities of the extracts were tested. The AcOEt extract from C. gracilis showed a moderate antibiofilm activity. Graphical abstract: Image 1 Highlights: 34 metabolites of diverse nature are identified through NMR analysis. T. lutea is characterized by PULCA, brassicasterol, squalene and DMSP production. FFA composition depend on the microalgae and FFA distribution in TG and MGDG differs. Dunaliella strains biosynthesize β-carotene and Chaetoceros and T. lutea fucoxanthin. DHSP production is shown as a distinctive feature of diatoms.